Electric Dipole Transition of the First Excited State of 9Be - M, Odsuren; K, Kato; G, Khuukhenkhuu; S, Davaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
The E1 transition strength of the 1/2+ first excited state of 9Be is calculated using three body cluster model and complex scaling method where the excited state is correctly treated as unbound. The 1/2+ resonance is obtained using the attractive three-body potential.